Analisa Penetapan Harga Pokok Produksi dengan Pendekatan Metode Activity Based Costing dan Full Costing dengan Mempertimbangkan Aspek Physical Distribution Service Quality (Studi Kasus: Laundry To-Go) - Cahyani, Putri Wulan; Erdhianto, Yoniv (Institut Teknologi Adhi Tama Surabaya, 2023)
Laundry To-Go provides services in washing, ironing, and others. Based on observations in the last few months, Laundry To-Go has experienced frequent problems, namely unexpected costs during the production process that have not been calculated yet and the absence of regular service quality measurements. This study aims to calculate the cost of goods manufactured and customer satisfaction with the services provided by Laundry To-Go. It employed the methods of activity-based costing (ABC), full costing, and physical distribution service quality. The results of this study indicated that the cost of goods manufactured in the ABC method was smaller than the traditional system, i.e., IDR 29,946 for pillow service, IDR 13,929 for sheet service, IDR 15,340 for bedcover service, IDR 34,908 for safari suit service, and IDR 32,755 for bolster service. Meanwhile, the result of the fixed cost for each service was IDR 35,043 for pillow service, IDR 14,330 for sheet service, IDR 15,756 for bedcover service, IDR 39,217 for safari suit service, and IDR 38,258 for bolster service. The total variable cost for each service was IDR 3,253 for pillow service, IDR 2,236 for sheet service, IDR 2.614 for a bedcover service, IDR 5.192 for safari suit service, and IDR 3.734 for bolster service. In conclusion, the service quality at Laundry To-Go reached 0.80, meaning that its customers were satisfied with the services provided.